Hydrogenated Nanocrystalline Silicon Thin Films Prepared by Hot-Wire Method with Varied Process Pressure - V. S. Waman; A. M. Funde; M. M. Kamble; M. R. Pramod; R. R. Hawaldar; D. P. Amalnerkar; V. G. Sathe; S. W. Gosavi; S. R. Jadkar (Journal of Nanotechnology)
Hydrogenated nanocrystalline silicon films were prepared by hot-wire method at low substrate temperature (200∘C) without hydrogen dilution of silane (SiH4). A variety of techniques, including Raman spectroscopy, low angle X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, atomic force microscopy (AFM), and UV-visible (UV-Vis) spectroscopy, were used to characterize these films for structural and optical properties. Films are grown at reasonably high deposition rates (>15 Å/s), which are very much appreciated for the fabrication of cost effective devices. Different crystalline fractions (from 2.5% to 63%) and crystallite size (3.6–6.0 nm) can be achieved by controlling the process pressure. It is observed that with increase in process pressure, the hydrogen bonding in the films shifts from Si–H to Si–H2 and (Si–H2)n complexes. The band gaps of the films are found in the range 1.83–2.11 eV, whereas the hydrogen content remains <9 at.% over the entire range of process pressure studied. The ease of depositing films with tunable band gap is useful for fabrication of tandem solar cells. A correlation between structural and optical properties has been found and discussed in detail.